2007
DOI: 10.1111/j.1478-3231.2007.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma producing a granulocyte colony‐stimulating factor: report of a resected case with a literature review

Abstract: A complete resection of a hepatocellular carcinoma (HCC) producing the granulocyte colony-stimulating factor (G-CSF) was performed and is reported here. The patient had a few general symptoms and complications, such as the paraneoplastic syndrome. He had marked granulocytosis, and his serum levels of G-CSF and interleukin-6 were elevated. The pathological findings of the resected specimen revealed poorly differentiated HCC with sarcomatous change and showed, immunohistochemically, staining of G-CSF. Only a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
(37 reference statements)
1
34
0
1
Order By: Relevance
“…3B), bladder carcinoma (46), hepatoma (47), squamous cell carcinoma (48), and gastric cancer (49). Under stressful or inflammatory conditions, G-CSF is expressed by normal cell lineages (35,46) in response to endotoxins from infectious bacteria (43), iNOS (35), TNFa, IL1b, and NF-kB activation (35,39).…”
Section: Discussionmentioning
confidence: 99%
“…3B), bladder carcinoma (46), hepatoma (47), squamous cell carcinoma (48), and gastric cancer (49). Under stressful or inflammatory conditions, G-CSF is expressed by normal cell lineages (35,46) in response to endotoxins from infectious bacteria (43), iNOS (35), TNFa, IL1b, and NF-kB activation (35,39).…”
Section: Discussionmentioning
confidence: 99%
“…Some solid tumors have been shown to produce substances with colony-stimulating activity. 148 Alternatively, leukocytosis may result from bone marrow involvement by tumor. Once other etiologies are ruled out, paraneoplastic granulocytosis does not require specific therapy.…”
Section: Paraneoplastic Hematologic Syndromesmentioning
confidence: 99%
“…[137][138][139][140] The clinical features, associated malignancies, diagnostic studies, and treatment of paraneoplastic hematologic syndromes are listed in Table 4. 137,138,[140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] eoSInopHIlIa Paraneoplastic eosinophilia represents a subset of secondary eosinophilia that appears due to tumor production of the eosinophil growth factors interleukin (IL)-3, IL-5, and GM-CSF. 137,157 By contrast, primary eosinophilia, a separate diagnosis encountered in hematology-oncology practices, often represents a clonal phenomenon caused directly by a hematologic neoplastic process.…”
Section: Paraneoplastic Hematologic Syndromesmentioning
confidence: 99%
“…HCC patients with a high IL-8 expression have a significantly higher frequency of venous invasion, portal vein invasion and bile duct invasion than HCC patients with a low IL-8 expression (4). Patients with G-CSF-producing HCC commonly have a very poor prognosis with rapid tumor growth and a high probability of distant metastasis (6)(7)(8). It has been reported that coproduction of G-CSF and IL-6 is associated with the production of IL-1, a known inflammatory cytokine, in G-CSF-producing cancer cell lines (9).…”
Section: Discussionmentioning
confidence: 99%